Pengaruh Model Problem Solving terhadap Kemampuan Berpikir Kritis Siswa pada Pembelajaran Biologi : Literatur Review - Tasya Khairani; Heffi Alberida (Al-Alam: Islamic Science Education Journal, 2026)
Critical thinking skills are an important competency in biology learning that needs to be developed through appropriate learning models. This study aims to examine the effect of the problem-solving model on students' critical thinking skills through a literature review. The study was conducted on scientific articles published between 2020 and 2025 and obtained through the ERIC and Google Scholar databases using the keywords problem-solving and critical thinking skills. The review results indicate that the application of the problem-solving model has a positive and significant effect on improving students' critical thinking skills. Students' active involvement in identifying problems, analyzing information, and formulating solutions based on scientific evidence trains students to think logically, reflectively, and systematically. The problem-solving model is effectively used as a biology learning strategy to develop students' critical thinking skills.